Oscillatory fluid flow and heat transfer through porous medium between parallel plates with inclined magnetic field, radiative heat flux and heat source - Mehta, Tripti; Mehta, Ruchika; Mehta, A. (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the paper is to investigate an oscillatory fluid flow and heat transfer through a porous medium between parallel plates in the presence of an inclined magnetic field, radiative heat flux and heat source. It is assumed that electrical conductivity of the fluid is small and the electromagnetic force produced is very small. The governing coupled equations of motion and energy are solved analytically. Numerical results for the velocity and temperature profiles, local skin friction coefficient and local Nusselt number for various values of physical parameters are discussed numerically and presented graphically.
Keywords: oscillatory; inclined magnetic field; porous medium; radiation; heat source; skin-friction coefficient; Nusselt number